Implementation Of The 4T+1M Method In Tahfizh Qur'an Lessons In MTs. Darul Ulum Budi Agung Medan - Aulyah Rabilla (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the implementation of the 4T + 1M method for learning Tahfidz Al-Qur'an in MTs. Darul Ulum Budi Agung. This research is a qualitative research using field research (Field Research). Data obtained in this study using interviews, observation and documentation. The data analysis used using the analytical model, Miles Nuberman. The results of this study, that the method is compiled in an applicative and effective manner, so as to provide convenience for students to be able to memorize the Qur'an properly and correctly in accordance with recitation and Makrojul letters. The implementation of the 4T + 1M method in MTs. Darul Ulum Budi Agung which is used in learning to read the Qur'an is held in grades VII to grade IX. The acquisition of the results of reading and memorizing the Qur'an to students using the 4T + 1M method showed a significant increase in accordance with the expected goals.